2017
DOI: 10.1007/10_2017_27
|View full text |Cite
|
Sign up to set email alerts
|

Specific Cell (Re-)Programming: Approaches and Perspectives

Abstract: Many disorders are manifested by dysfunction of key cell types or their disturbed integration in complex organs. Thereby, adult organ systems often bear restricted self-renewal potential and are incapable of achieving functional regeneration. This underlies the need for novel strategies in the field of cell (re-)programming-based regenerative medicine as well as for drug development in vitro. The regenerative field has been hampered by restricted availability of adult stem cells and the potentially hazardous f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 216 publications
0
4
0
Order By: Relevance
“…Ultimately, avoidance of any stably integrating programming as well as selection cassettes is of course highly desirable. In this regard, multiple cardiac differentiation protocols have meanwhile been published [72][73][74]. It remains to be seen whether an ultimate protocol fully reproducible between labs in the field as well as between different cell lines will emerge.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ultimately, avoidance of any stably integrating programming as well as selection cassettes is of course highly desirable. In this regard, multiple cardiac differentiation protocols have meanwhile been published [72][73][74]. It remains to be seen whether an ultimate protocol fully reproducible between labs in the field as well as between different cell lines will emerge.…”
Section: Discussionmentioning
confidence: 99%
“…It remains to be seen whether an ultimate protocol fully reproducible between labs in the field as well as between different cell lines will emerge. On the other hand, avoidance of stable introduction of programming factor DNA constructs could be achieved via use of modified mRNA or non-integrating viral vectors [72][73][74].…”
Section: Discussionmentioning
confidence: 99%
“…In drug development, pharmacological compounds are classified in respect to their cardiotoxic effects based on the AP or/and FP pattern in iPSC-derived CMs [34]. In addition, electrophysiology is used to identify and characterize the different cardiac subtypes in iPSC derived CM populations, which is crucial for specific cell programming strategies [20,66,67].…”
Section: Action Potential Vs Field Potentialmentioning
confidence: 99%
“…Moreover, it has largely been shown that iPSC-CMs represent a heterogeneous population of electrophysiological phenotypes, i.e., atrial, ventricular and nodal-like cells [19], each characterized by a specific electrical profile. Therefore, it is important to obtain electrophysiological data for detailed characterization of iPSC-CMs, in particular when differentiation into a certain cardiac subtype is desired [20,21].…”
Section: Introductionmentioning
confidence: 99%